IMPLEMENTATION OF ‘’PESANTREN KILAT’’ ACTIVITIES DURING RAMADAN TO DEVELOP THE PERSONALITY OF INMATES IN CLASS IIA PRISON BENGKULU - Khalifah, Bani; Yuska, Syahrial (Universitas Nusa Cendana, 2025)
This study examines the implementation of the Pesantren Kilat (short-term Islamic boarding school) program during Ramadan to develop the personality of prisoners at Class IIA Bengkulu Penitentiary. This research employed a qualitative method, collecting data through field observations, interviews, and literature studies. Data analysis was conducted using data reduction techniques and the NVIVO 12 software to identify themes and keyword frequencies such as